Kampung Taman’s Corridor Structure Investigation: A Territorial Analysis by Using a Snapshot Method - Clinton Tedyardi; Fermanto Lianto; Rudy Trisno; Denny Husin (Journal of Regional and City Planning, 2022)
Communality is prime in kampungs; the phenomenon of collective activities in kampungs is reflected in their structure, especially in the network of corridors, i.e., the in-between spaces that are the topic of this research. This research explored territorial analysis by converting photographs into architectural mapping diagrams and photo-collages using the snapshot method. The diagrams were produced to highlight the collective structure and the actual processes of communality. The physical structure was investigated as a medium to accommodate everyday activities in Kampung Taman, Yogyakarta, presenting a territorial analysis with respect to: a) implementation/execution, including activities, expressions, spaces, and joint structures; b) circulation; and c) dynamic phenomena occurring in Kampung Taman. The investigation illustrates a territorial implementation involving the physical structure of Kampung Taman’s corridor network and the user’s interpretation of space when conducting communal activities. This involves sharing social, communal, and public spaces. The territorial activities that affect the Kampung’s physical structure were tracked. The novelty is the discovery of spatial patterns that suggest organic development of the corridor network, as illustrated by a compilation of diagrams composed of strong examples captured directly on-site from Augustus 2018 to November 2020.